An Ethical Code for Commercial VR/AR Applications - Ramirez, Erick Jose; Tan, Jocelyn; Elliott, Miles; Gandhi, Mohit; Petronio, Lia (Intelligent Technologies for Interactive Entertainment, 2021)
The commercial VR/AR marketplace is gaining ground and is becoming an ever larger and more significant component of the global economy. While much attention has been paid to the commercial promise of VR/AR, comparatively little attention has been given to the ethical issues that VR/AR technologies introduce. We here examine existing codes of ethics proposed by the ACM and IEEE and apply them to the unique ethical facets that VR/AR introduces. We propose a VR/AR code of ethics for developers and apply this code to several commercial applications.